Implementasi Metode Pembelajaran Pendidikan Agama Islam di SMP Muhammadiyah Boarding School Kampung Sawah - Rizki Amrillah; Ahmad Abimubarok (Universitas Muhammadiyah Prof Dr Hamka, 2022)
Learning methods are an essential component in the implementation of learning in schools. The learning method is a way of conveying a theory or idea to facilitate the process of managing the theory so as to produce a complete understanding and mastery of the subject. If the implementation of Islamic Religious Education learning methods is appropriate, it will have an impact on increasing the values ​​of religiosity, spirituality and academic achievement. . The purpose of this study was to observe the implementation of the learning method for Islamic Religious Education subjects at the Muhammadiyah Boarding School Middle School at Kampung Sawah. This research is a qualitative research using observation and interview methods. The results of the study showed that the Islamic Religious Education teachers at SMP Muhammadiyah Boarding School Kampung Sawah still use lecturing and question-and-answer method, nevertheless for Arabic subjects, the method used is talqin method (Delivering). The teachers also did not make RPP (Learning Implementation Plans) because they did not know how to make it and were also not asked by the school. In learning, teachers prioritize close relationships with students compared to determining learning methods.